Pengendalian Kejadian Gugur Bunga dan Buah (Fruit-drop) dengan Aplikasi Indole Acetic Acid (IAA), Indole Butyric Acid (IBA) dan Giberelin Pada Tanaman Cabai (Capsicum annuum L.): Pengendalian Kejadian Gugur Bunga dan Buah (Fruit-drop) dengan Aplikasi Indole Acetic Acid (IAA), Indole Butyric Acid (IBA) dan Giberelin Pada Tanaman Cabai (Capsicum annuum L.) - Rahmansyah Dermawan; Ifayanti Ridwan Saleh; Katriani Mantja; Hari Iswoyo; St Salmiati (Universitas Bangka Belitung, 2020)
The study aimed to obtain morphophysiology information on fruit-drop events in chili plants on application of plant growth regulator (PGR) auxin (IAA and IBA) and gibberellins. The study was arranged based on a split-plot design in a randomized block design with 3 replications. The main plot is 3 types of PGR namely IAA, IBA, and GA3. The subplots are 5 levels of concentrations (ppm): 0, 25, 75, 50, and 100. The data were analyzed using STAR software and Smallest Significant Difference (LSD) 5%. The results showed that the application of PGR and concentration did not significantly affect the number of attached and abscised flowers. However, the application of PGR resulted in a higher number of attached flowers than the abscised flowers. Giving IAA 25 ppm produced the highest number of fruits compared to other IAA concentrations. Increasing the concentration of GA3 tends to increase the number of attached fruits and the highest at 100 ppm GA3. The interaction between PGR and concentration significantly affected the weight per fruit. The treatment of GA3 100 ppm produces the highest weight per fruit. Increasing the concentration of auxin tends to reduce the weight per fruit. The IBA 100 ppm decreases the length of chili.